COMPUTER PROGRAM FOR GENERATING MUSICAL COMPOSITIONS BASED ON THE AUTHOR'S MELODY - КУЦЬ, Н. М.; ПИЛИПЕНКО, Ю. М. (Technologies and Engineering, 2023)
Purpose. Finding and implementing ways to integrate a conceptual approach to create new musical compositions. Methodology. A set of conceptual components of a musical composition is singled out. In designing the software system, the principle of pure SOLID architecture was used. The design of algorithms is based on the “divide and conquer” paradigm. Findings. Algorithms have been developed, a program in the Kotlin programming language has been written and debugged, which allows working on editing a musical composition at a conceptual level - editing conceptual relationships, rather than specific note parameters. The volume of the program is about 16 thousand operators. Testing of the program showed that using it allows you to speed up the musical processing of a composition by about 10,000 times compared to manual editing. It is clear that the final decision on the success of editing is made by the author, but now he has the opportunity to listen to various versions of the processed composition, which, in fact, he does not spend time creating. Originality. A new approach to the use of a computer when writing musical compositions is proposed, when, based on the author's melody, a computer program generates, according to the laid down templates, somewhat modified accents of the sound of the work (for example, in terms of timbre, key, rhythm, etc.). This approach is implemented in the form of a computer program, the use of which accelerates the generation of musical works in which the author's melody sounds thousands of times. Practical value. The written software product allows the composer to effectively use the new possibilities of creating musical compositions based on the author's melody.